LIFESTYLE PROFILE, LEISURE AND RISK CONTROL FACTORS OF YOUNG AND ADULT EDUCATION STUDENTS - VENÂNCIO AIRES - RS (Fiep Bulletin - online, 2013)
The study, of a descriptive-exploratory approach, conducted with 138 students, of both genders, aged 16 to 55, had the aim to characterize the lifestyle profile, leisure and control of risk factors of the Young and Adult Education (EJA) students, of a state school in the county of Venâncio Aires, RS. Through the results (obtained through the Lifestyle inventory), we ascertained that: at home, both genders are fond of watching television, listening to music and talking with friends, common to boys and girls; the girls, in particular, help with house chores. Outside the home, in both genders, a preferred activity is talking with friends, going for a walk. Boys, in particular, have other habits of note, like cycling and playing soccer (of course, soccer adjusted to the available spaces). With regard to health concerns, thirty minutes of physical activity, three times a week, is more common with the males. Regarding health risks, the women know their blood pressure more than the men; in both genders, there are high rates of carelessness towards the ingestion of fatty foods and sweets. More men than women cherish friends and are happy with their relationships and most of them admit having difficulty achieving a balance between the personal and professional life. Our conclusion was the E.J.A. students' lifestyle is little active, and sedentary habits are particularly common with the women. In both genders, there is difficulty promoting health and avoiding health risk factors (high blood pressure, particularly in males, and obesity). It is recommended to make these students aware of the need to revise their daily habits and, consequently, achieve a better quality of life.
Keywords: lifestyle; leisure; risk control factors